A NEW SPECIES OF RIEDELIA (ZINGIBERACEAE) FROM PAPUA, INDONESIA - Newman, M. F. (Edinburgh Journal of Botany, 2010)
A new species of Riedelia (Zingiberaceae), Riedelia charontis M.F.Newman from Papua Province, Indonesia, is described and illustrated.
Keywords: Indonesia; new species; Papua; Riedelia; Zingiberaceae